Prospective longitudinal follow‐up of children with sickle cell disease treated with hydroxyurea since infancy. Issue 9 (3rd June 2019) - Thomas, Ronay; Dulman, Robin; Lewis, Angela; Notarangelo, Bailey; Yang, Elizabeth
Abstract: Background: Hydroxyurea (HU) increases fetal hemoglobin (HgbF) and ameliorates sickle cell disease (SCD) symptoms. Studies have demonstrated the safety and efficacy of HU in infants and children. Initiation of HU in infancy for children with SCD needs to be implemented in community practice. Procedure: Starting in 2011, the Pediatric Sickle Cell Program of Northern Virginia initiated HU in infants with SCD. A prospective longitudinal database tracked the clinical course and outcomes. Results: Twenty‐four children with HgbSS who started HU by age 1 were continuously followed for a total of 95 person‐years. Age at the time of analysis ranged from 2 to 7 years. Average hemoglobin at 6‐month intervals ranged from 9.5 + 1.9 to 10.7 + 0.8 g/dL, and average HgbF ranged from 27.8 + 5.0% to 34.1 + 6.6%. Twenty‐seven hospitalizations occurred (0.28/person‐year), all before age 3, including 19 (70%) for fever or infection, five (19%) for splenic sequestration, and one (4%) for pain in an infant prior to starting HU. The treat‐and‐release emergency department visits totaled 68 (0.72/person‐year), including 62 visits (91%) for fever, infection, or viral illness, and two visits (3%) for pain/dactylitis in infants before HU initiation. Splenic sequestration accounted for all five transfusions. No pain episodes requiring medical attention were documented after HU initiation. No complicated acute chest syndrome, no abnormal or conditional transcranial Doppler ultrasound, and no overt strokes occurred. Conclusion: Implementation of HU in infancy for patients with SCD in community practice is feasible and is highly effective in preventing disease complications.